PENGARUH KUALITAS PRODUK DAN PELAYANAN TERHADAP KEPUASAN KONSUMEN - Petra Paulus Tarigan (EQUILIBIRIA, 2017)
This study aims to determine the effect of the quality of products and services to customer satisfaction. In this study, customer satisfaction is the dependent variable. There are two variables that serve as the independent variable is the quality of products and services. The sample used in the study is that consumers. The population used in this study is 60 consumers. While the sample used as many as 60 by using the census as a population of less than 100 people, then it is better researched everything. Data analysis method used is multiple regression analysis, which aims to determine the correlation between the two variables. Hypothesis testing is done by t test and F test and R2 test. Analysis of the data with the help of statistical data processing software SPSS version 20. Based on this study concluded: there is a positive and significant influence between product quality and consumer satisfaction, and no significant positive effect between service and customer satisfaction, as well as a positive and significant influence between product and service quality to customer satisfaction. The variable quality of the product into the variables dominant influence on customer satisfaction is based on the calculation of beta coefficients Standarized analysis has the greatest value. The conclusion from this study is the quality of products and service as important variables that affect customer satisfaction. Therefore, it is recommended that the company pay more attention these two variables so that consumers feel satisfied and achieve the objectives of the company are expected.